Curing kinetics of epoxies by thermal and alternative radiation in the application of fibre-reinforced composites - Ng, Feng Lin. (2011)
Fibre reinforced composite materials have become an alternative to many structural materials such as steels and alloys and some have become the dominant form of structural material. A major challenge faced by the fibre-reinforced composites industry is the presence of volatile organic compounds (VOCs) in hardener and solvent and the time taken for thermal curing is considerably long.